تكامل منهج سيجما سته "Six Sigma" وبطاقة الأداء المتوازن "BSC" وعلاقته بالاداء المالي في الشركات الصناعية المساهمة العامة الفلسطينية - الكببجي، مجدي وائل (جامعة القصيم - كلية الاقتصاد والإدارة, 2019)
هدفت الدراسة إلى التعرف على التكامل بين منهج سيجما ستة (Six Sigma) وبطاقة الأداء المتوان (bsc) وعلاقته بالأداء المالي في الشركات الصناعية المساهمة العامة الفلسطينية، وذلك من خلال التعرف على العلاقة بين منهج سيجما ستة وأبعاد بطاقة الأداء المتوازن المتمثلة في (بعد العملاء، البعد المالي، بعد التعلم والنمو، بعد العمليات الداخلية، البعد الاجتماعي)، وتوضيح تأثير متغيرات الأداء المالي (حجم المبيعات، العائد على الأصول، العائد على الاستثمار، التدفقات النقدية الحرة) على التكامل بين منهج سيجما ستة وأبعاد بطاقة الأداء المتوان. ومن أجل تحقيق أهداف الدراسة، تم استخدام المنهج الوصفى التحليلي، من خلال تصميم استبانة وزعت على عينة الدراسة المتمثلة في العاملين الإداريين في الشركات الصناعية المساهمة العامة المدرجة في بورصة فلسطين، والتي يبلغ عددها (١٣) شركة، تم توزيع (٨٤) استبانة، وتم استرداد (٧٣) استبانة. كما استخرجت البيانات المالية من التقارير المالية المنشورة للشركات للعام ٢٠١٧. وقد توصلت نتائج الدراسة إلى أن الشركات الصناعية المساهمة العامة الفلسطينية تطبق مدخل التكامل عبر تركيز الشركات على الاستفادة من المنافع المتولدة من التكامل بين منهج سيجما ستة وبطاقة الأداء المتوازن، ووجود أثر وعلاقة طردية بين منهج سيجما ستة وأبعاد بطاقة الأداء المتوازن، كما تبين وجود تأثير لمتغيرات الأداء المالي المتمثلة بــ (حجم المبيعات، العائد على الأصول، والعائد على الاستثمار) على التكامل، وعدم وجود أثر لمتغير (التدفقات النقدية الحرة) على التكامل بين المنهجين. وقد قدم الباحث مجموعة من التوصيات، من أهمها: ضرورة التوجه نحو إعداد الكوادر المهنية المدربة تدريبا معتمدا على تطبيق منهجية سيجما ستة، وكذلك على كيفية التعامل مع بطاقة الأداء المتوازن، وضرورة توعية ودعم الجهاز الإداري وخاصة الإدارة العليا بأهمية تطبيق التكامل، من أجل الاستجابة للمتغيرات البيئية السريعة.
This study aims at identifying the integration between Six Sigma approach and Balanced Scorecard (BSC) and its relationship to the financial performance of Palestinian Shareholding Industrial companies. By identifying relationship between the Six Sigma approach and the dimensions of the Balanced Scorecard (BSC) of (Customer perspective, Financial perspective, Learning and development perspective, Internal processes perspective, the Social perspective), it seeks to clarify the effect of using financial performance variables expressed by the proxy of (Sales Size, Return on Assets, Return on Investment, Free Cash Flows) executed on integration. To achieve the objectives of the study, the descriptive analytical approach has been used. A questionnaire was designed and distributed to administrative employees in the Companies. Thirteen companies have represented the study sample, Eighty-four questionnaires were distributed, and seventy-three questionnaires were collected. The financial statements were also extracted from published financial reports for companies 2017. The findings show that the Palestinian industrial companies apply the integration approach by concentrating companies to take advantage of the benefits generated by integration. It reveals that these benefits increase by the effect of a positive relationship between the Six Sigma approach and the dimensions of the Balanced scorecard, there is the effect of the financial performance variable (Sales Size, Return on Assets and Return on Investment) on the integration of Six Sigma and Balanced Scorecard, and The absence of an effect on the variable (Free Cash Flows). The study concludes with recommending that the participating companies should develop and invest in a base of highly trained personnel on Six Sigma techniques and BSC methodology in order to increase their ability in measuring and improving their performances. It also suggests that the administrative body, especially the senior administration, needs to sensitive and support the application of integration in order to respond to rapidly changing environment.
Keywords: بطاقات الاداء المتوازن -- الشركات الصناعية -- فلسطين -- الاستثمار المالي